Internalisasi Nilai-Nilai Luhur Tradisi Nyadran dalam Pendidikan Karakter di Era Modernisasi - bhaharuddin yusuf, Jaya (Education Reserach Center, 2025)
The Nyadran tradition, a Javanese cultural heritage, embodies noble values such as religiosity, gratitude, mutual cooperation, and pluralism, which are increasingly overlooked amidst modernization. This study explores these values and their relevance to character education in the face of globalization's challenges. Employing a qualitative library research approach, it analyzes literature on Nyadran, cultural values, and modernization's impact. Findings indicate that the younger generation's understanding of Nyadran's philosophical essence is diminishing, reducing the tradition to a mere ceremonial act. To counter this, revitalization strategies are proposed, including early cultural education, community empowerment, technology-driven innovations like digital documentation and social media campaigns, and supportive government policies. These efforts aim to preserve Nyadran not only as a ritual but as a vital tool for fostering character education, social cohesion, and national identity in the modern era.